Semantic shifts in EU competition law: A data-driven study of policy goals - Anselm Küsters (EconPol Forum, 2024)
Text mining and corpus linguistic methods are used to analyze 11,000 EU competition law decisions and judgments. This reveals a shift in the competition vocabulary from ordoliberalism in the 1970-80s to neoliberalism in the post-2000s. While the Commission has partly adopted a neoliberal vocabulary, the courts have stuck to ordoliberal rhetoric. This shift in economic thinking is also reflected in enforcement actions and institutional priorities. Understanding semantic shifts in EU law is crucial to aligning policy with underlying theories and doctrines.
Keywords: 330